Математичні моделі та методи розв’язання задач дифузії під час прогнозування продажів - Фірулін, С. О. (ХНУРЕ, 2023)
The Bass model or Bass diffusion model was developed by Frank Bass. It consists of a simple differential equation that describes the process of how new products get adopted in a population. The model presents a rationale of how current adopters and potential adopters of a new product interact. The Bass model has been widely used in forecasting, especially new products' sales forecasting and technology forecasting. Mathematically, the basic Bass diffusion is a Riccati equation with constant coefficients.
Keywords: задача дифузії; прогнозування продажів; модель дифузії Басса